Caring and Coping in the City of Dogs: Review of Chris Pearson, Dogopolis: How Dogs and Humans Made Modern New York, London, and Paris - Howell, Philip (Humanimalia, 2022)
Review of Chris Pearson, Dogopolis: How Dogs and Humans Made Modern New York, London, and Paris. Animal Lives. Chicago: Chicago University Press, 2021. 259 pp.; 21 illus. 24.00 (pb), 95.00 (hb).